LEVEL BERPIKIR SISWA BERDASARKAN TEORI VAN HIELE DITINJAU DARI SELF CONFIDENCE DI SMP - Andriani, Riska Putri; Jamiah, Yulis; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to analyze the level of thinking of students based on Van Hiele's Theory on the material obtained rectangular flat in terms of self-confidence. The method used in this research is descriptive qualitative. The subjects in this study were six eighth grade students of SMP Negeri 1 Teluk Pakedai. The data collection techniques used in this study were and interview, wich were given to the chosen subjects based self-confidence categories. The results of data analysis showed that there were two students who were at the level of visualization, three students who were at the level of analysis, and one student who was at the level of abstraction. The level of thinking students in visualization shows in terms of the confidence obtained by students catching a rectangle from the interpretation of the interpretive form without understanding the regularity of the shape, using the properties that are not appropriate in accordance with determining the quadrilateral. When the analysis is obtained students can tell about how to get the properties that appear at the top can explain the nature of getting special. At the same time, student are not able to connect the same properties between one quadrilateral build and another. Keywords : Self Confidence, Thinking Level, Van Hiele Theory